Saluran Gendong Sebagai Proteksi Sedimentasi Aliran Permukaan Dari Lahan Tambang Batu Bara Pada Saluran Irigasi D.I. Tapin - Gleny Floresa Wirdyanata (Lambung Mangkurat University Press, 2022)
Construction of irrigation network D.I. Tapin is projected to serve 5,472 hectares of rice fields. In the process the irrigation canal through various types of land, including ex-mining land, which has an impact on the existing irrigation canal filled with mud from ex-coal mining land every rainy season on the BTKN 5 – BTKN 6 section. This causes the downstream flow to be cut off. Therefore, it is necessary to protect irrigation canals from surface runoff that carries sedimentary material. There are 2 alternative solutions, namely changing an open channel into a closed channel using a culvert structure, or adding a carrying channel to protect irrigation channels from run off outside the irrigation area. The two alternatives were analyzed for cost, time, quality, implementation method, as well as operation and maintenance. It was concluded that the solution to this problem was to use alternative II, namely the work of a carrying channel as a protection for surface runoff sedimentation from coal mines in the D.I Irrigation Channel. This is due to the 21 days faster processing time, simpler implementation method, easier operation and maintenance, and a higher cost of Rp. 225,490,090 is still within reasonable limits by service users.